Sweet reason : a field guide to modern logic - Henle, James M.; Garfield, Jay L., 1955-; Tymoczko, Thomas (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2011)
"Sweet Reason: A Field Guide to Modern Logic, 2nd Edition offers an innovative introduction to logic that integrates formal first order, modal, and non-classical logic with natural language reasoning, analytical writing, critical thinking, set theory, and the philosophy of logic and mathematics. An innovative introduction to the field of logic in all its guises, designed to entertain as it informs Addresses contemporary applications of logic in fields such as computer science and linguistics A web-site linked to the text features numerous supplemental exercises and examples, enlightening puzzles and cartoons, and insightful essays"--
Includes index.
Keywords: Logic, Modern -- 20th century